2008
DOI: 10.1007/s00441-008-0649-x
|View full text |Cite
|
Sign up to set email alerts
|

The prophenoloxidase system is activated during the tunic inflammatory reaction of Ciona intestinalis

Abstract: Phenoloxidase (PO) activity was examined in the tunic tissue of Ciona intestinalis following lipopolysaccharide (LPS) intratunic injection. Tunic homogenate supernatant (THS), assayed with the Dopa-MBTH reaction, displayed Ca 2+ -independent PO activity that was raised by LPS and further enhanced by proteases. Specific inhibitors (tropolone, phenylthiourea, diethylthiocarbamate) supported the specificity of the reaction. Assay with soybean trypsin inhibitor showed that, in the tunic, PO activation with trypsin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 43 publications
5
31
0
Order By: Relevance
“…Previous findings on inflammatory genes expression, including CiTNFα and galectins (Vizzini et al, 2012), revealed a prompt (4-8 h) upregulation of immune-related genes transcription by pharynx hemocytes, and the present paper suggest that CiIL17 genes, such as vertebrate ortologs, are involved in the inflammatory response (Parrinello et al, 2007Vizzini et al, 2012). In situ hybridization assay showed that CiIL17 genes are expressed by inflammatory hemocytes (granulocytes and URGs) in the pharynx vessels, and, according to previous findings (Bonura et al, 2009(Bonura et al, , 2010Cammarata and Parrinello, 2009;Cammarata et al, 2008;Parrinello et al, 2008Parrinello et al, , 2010Vizzini et al, 2008Vizzini et al, , 2012, the LPS inoculation enhanced the population density of hemocytes expressing immune-related genes including CiIL-17s. Finally these findings suggest that CiIL-17 genes may be key genes in cellular defence reaction.…”
Section: Discussionsupporting
confidence: 85%
“…Previous findings on inflammatory genes expression, including CiTNFα and galectins (Vizzini et al, 2012), revealed a prompt (4-8 h) upregulation of immune-related genes transcription by pharynx hemocytes, and the present paper suggest that CiIL17 genes, such as vertebrate ortologs, are involved in the inflammatory response (Parrinello et al, 2007Vizzini et al, 2012). In situ hybridization assay showed that CiIL17 genes are expressed by inflammatory hemocytes (granulocytes and URGs) in the pharynx vessels, and, according to previous findings (Bonura et al, 2009(Bonura et al, , 2010Cammarata and Parrinello, 2009;Cammarata et al, 2008;Parrinello et al, 2008Parrinello et al, , 2010Vizzini et al, 2008Vizzini et al, , 2012, the LPS inoculation enhanced the population density of hemocytes expressing immune-related genes including CiIL-17s. Finally these findings suggest that CiIL-17 genes may be key genes in cellular defence reaction.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, a future research direction might be the possibility that this cell gathered in clusters could represent epithelia host stationary cells derived from the lymph nodules (Ermak, 1976). According to previous findings Vizzini et al, 2008Vizzini et al, , 2012Cammarata et al, 2008;Bonura et al, 2009Bonura et al, , 2010, the LPS inoculation enhanced the population density of hemocytes expressing immune-related genes including CiTGF-b. In invertebrates, TGF1 affects immunocyte and human monocyte migration in dose-correlated fashion and induces hemocytes to migrate in a chemotactic manner (Ottaviani et al, 1997a).…”
Section: Discussionsupporting
confidence: 59%
“…It is known that during a pathogenic infection, the expression of galectin genes is often upregulated and their production increase [2,4]. The LPS locally inoculated through the ascidian body wall directly permeates the underlying pharynx tissue and stimulates a prompt local inflammatory reaction including upregulation of collagen-IX-like, C3a [43], TNFalfa-like [23,24] and MBL-like genes [25], together with enhanced phenoloxidase activity [22,44] and an overproduction of galectin-like molecules with opsonic properties found in the hemolymph [27]. Here we show that LPS promptly upregulates CiLgals-a and -b genes being CiLgals-a more represented as shown by a higher expression rate.…”
Section: Discussionmentioning
confidence: 99%